FACTORS ASSOCIATED WITH HYPERTENSION AMONG POSTMENOPAUSAL WOMEN IN PARANGTRITIS COASTAL AREA IN BANTUL, YOGYAKARTA, INDONESIA - Pratama, Yanasta Yudo (Universitas Ahmad Dahlan, 2021)
Background: Blood pressure tends to increase in women associated with menopause. Thus, post-menopausal women more often had hypertension than pre-menopausal. One of the risk factors for hypertension is high blood cholesterol levels (hypercholesterolemia). Meanwhile, people who live in coastal areas can suffer from hypertension, which is higher than in rural or mountain areas.Objective: To study the factors associated with hypertension among post-menopausal women in Parangtritis Coastal Area.Method: We used an observational study using the Case-Control design conducted in Parangtritis village, Kretek subdistrict, Bantul district, in June-July 2013. Amount 62 respondents were recruited using consecutive sampling consist of 31 people for each case and control—data obtained from primary data (measurements and interviews). Analysis war performs using descriptive and the Chi-Square test.Results: Among the three risk factors we assessed, age and BMI significantly affect post-menopausal women's hypertension. At the same time, total cholesterol is not a risk factor for post-menopausal women to get hypertension.Conclusion: There was an association between age, BMI, and hypertension among post-menopausal women in Parangtritis coastal area. In contrast, total cholesterol was not a risk factor for post-menopausal women to get hypertension.